EVALUASI SISTEM PELAYANAN ONLINE DALAM PEMBUATAN KARTU KELUARGA PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN TULANG BAWANG - angelina, refi (JURNAL SOSIAL DAN HUMANIS SAINS, 2022)
The purpose of this study was to find out the system, availability of information, form of service and feedback from the application of family card services at the Department of Population and Civil Registry of Tulang Bawang Regency. The research method using this research location was carried out at the Office of Population and Civil Registry located in Tulang Bawang Regency. The selection of the research area and location for the reason that the researcher wanted to know the problem of the agency's family card service. This type of qualitative research uses data sources consisting of primary data and secondary data. The research informants consisted of the head of the service, employees and the community who used the family card service. Data collection techniques used observation and interview guidelines. Data analysis techniques include data reduction, data presentation and verification. the results of the study found that the system derived from the application of family card services with online and offline systems had been implemented according to the input, process and output of data for applicants who must have a family card and have been registered in the online system in the national population database. Availability of information from the application of the family card service has been adapted to the needs of obtaining objective, subjective and general information. The form of feedback from the application of the family card service has been followed up by employees according to suitability, effectiveness, timeliness and procedural origin of the family card issuance service activity.